Implementation of Religious Character Values in Scout Activities at Junior High School South Lampung - Mawadda, Novziah; Anwar, Chairul; Jatmiko, Agus (Bulletin of Science Education, 2024)
In Indonesian education, the imperative challenge of cultivating robust character among the youth has surfaced prominently over the past decade, recognizing character's pivotal role in a nation's success trajectory. Innovative strategies, including the early integration of religious character values within educational settings like scout activities, become crucial responses to this challenge. Scout activities, renowned for their holistic approach to character development, serve as critical platforms in moulding religious character among students. This research aims to achieve three primary objectives: identifying embedded religious character values within Scout activities, exploring implementation methodologies, and investigating facilitating or hindering factors. The study navigates the intricate dynamics of religious character integration through a qualitative lens and employs semi-structured interviews, non-participant observation, and documentation analysis. The findings underscore the significance of rituals, notably communal prayers, as fundamental avenues for instilling religious values alongside activities promoting environmental stewardship deeply rooted in Islamic teachings. By elucidating the multifaceted role of Scout activities in nurturing religious character, this study contributes to the discourse on character education, offering insights for educators and policymakers to strengthen the moral fabric of future generations. Keywords: Religious Character Values, Scout Activities, Religious Character Integration